SPATIAL DEVELOPMENT OF CILIMUS MARKET AREA KUNINGAN DISTRICT - Lidiawati, Puput Putri; Firmanto, Arief (Journal of Green Science and Technology, 2019)
Cilimus Market is located in Desa Cilimus, Kecamatan Cilimus, Kabupaten Kuningan-Jawa Barat. For Cilimus Market conditions, it?s now starting to become irregular, such as parking lots being used as a place to sell, spaces in the stuffy market, air circulation is not good, types of traders are not separated according to the block, market space capacity is not in accordance with the number of visitors and traders. And often experience traffic jams around the Cilimus Market area due to vehicles parked along the road.So that to overcome these problems needed a solution. First, to determine the determination of market development strategies using the analysis method of Strengths Opportunities Aspirations Results (SOAR), both projections of the number of traders are projected for 2023. Then planning the market building becomes 3 (three) floors with the addition of facilities and infrastructure facilities and market spatial plans based on SNI 8152: 2015 regulation on the People's Market designed with Autocad and SketchUp. And for the Cilimus Market area such as Taman Cilimus and Terminal Cilimus developed by adding infrastructure facilities in accordance with RDTR Kecamatan Cilimus Tahun 2014 and Peraturan Direktorat Perhubungan Tahun 1996.The results of this thesis research are Cilimus Market was developed into a Modern Market with it's constructed 3 floors and to Cilimus Market area added other facilities according to existing regulations.Keywords : Market Development, Market Spatial Planning, SOAR Analysis.